Authors and Apparatus : A Media History of Copyright - Dommann, Monika (Book collections on Project MUSE., 2019)
"Copyright is under attack. This book charts the development of this conflict in the U.S., Germany, France, and Great Britain and uses the examples of photocopy and sound recording to outline the complex rights and interests of all relevant parties from 1850 to the present day"--